CALCULATION OF PRESCRIBED DAILY DOSE OF ANTICOAGULANTS IN SOUTH INDIAN POPULATION - K, Venkateshwarlu; Tp, Joshua Jacinth; G, Praneeth; G, Anusha; Goud N, Rahul (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study were to identify the commonly prescribed anticoagulants and to study the prescription pattern of anticoagulants in various indications and to calculate prescribing daily dose (PDD) and to compare PDD with defined daily dose of anticoagulants. Methods: A total of 119 patients of all age groups, either of sex who are receiving anticoagulant therapy were included in this prospective observational study done in limited period of 6 months in the inpatient department of general medicine, gynecology, pediatrics, and surgery. Patients who are non-cooperative, cancer patients, psychiatric patients, and patients on hemodialysis and receiving anticoagulant treatment, and patients suffering from end-stage renal disease and hepatic failure are excluded from the study. Results: In this study, we found that heparin, Low-molecular-weight heparins (LMWHs), warfarin, and acenocoumarol are the most commonly used drugs, of which heparin is highly prescribed. The use of anticoagulants in cardiovascular diseases was found to be high compared to other indications. PDD: DDD of warfarin is 0.46, acenocoumarol is 0.75, i.e., half the dose of drug showed its effectiveness, whereas heparin is 1.86, LMWH's is 2.9, i.e., double the dose is used to treat the disease effectively. A total of eight adverse drug reactions are observed with Vitamin K antagonists, i.e., 6.72%. Conclusion: We observed that the anticoagulants were not prescribed as the WHO defined doses in the study site. Vitamin K antagonists were prescribed at half of the WHO defined doses and heparin derivatives were prescribed at increased doses and sometimes double the WHO defined doses; these variations may be due to disease characteristics or patient characteristics or drug characteristics.